Status of Cileuleuy Swamp Waters in Taman Buru Masigit Kareumbi Area, West Java Province, Based on Physicochemical and Macrobentic Factors - Septianingrum, Sani
The Cileuleuy Swamp, covering an area of 4,19 Ha at an altitude of 1135 meters above sea level, is the largest swamp in the Taman Buru Masigit Kareumbi (TBMK) with its main function as a water reservoir for the local community. Monitoring the condition of swamp ecosystem in TBMK area has never been done so this study aims to determine the status of Cileuleuy Swamp Waters by using the Rondo (1982) scoring system. The parameters measured are color, odor, temperature, conductivity, Total Suspended Solid (TSS), Total Dissolved Solid (TDS), dissolved oxygen content, pH, turbidity, along with amonium, nitrate, nitrite, orthophosphate content in water and macrobenthos diversity. Water and macrobenthos samples were taken in March and May 2019 at five sampling points. Water color and odor scores were determined qualitatively while physicochemical parameters were determined quantitavely. Sampling of macrobenthos samples was done by Eckman grab and identified using some reference books including Thorp and Covich (2015) and Yule and Sen (2004) then determined its Shannon-Wiener diversity index and Simpson Dominance index. The results showed no difference in physicochemical parameter scores between March and May 2019 with the tendency for water to become eutrophied. Seven macrobenthos families were found, namely Chironomidae, Hydropsychidae, Formicidae, Dytiscidae, Baetidae, Synlestidae, and Scirtidae with Shannon- Wiener diversity index 1,57 in March and 1,70 in May along with Simpson dominance index 0,25 in March and 0,22 in May which indicated the macrobenthos community in Cileuleuy Swamp according to Maguran (1998) category was included in the medium diversity category and there were no dominating families.The final score for the status of Cileuleuy swamp waters based on the Rondo scoring system both in March and May is 2,71 which shows the status oof Cileuleuy swamp waters is lightly polluted.